Penerapan Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar IPAS Siswa Kelas V SD 5 Jurang - Sa'adah, Nailis; Ismaya, Erik Aditia (Jurnal Ilmiah Wahana Pendidikan, 2024)
The primary objective of this investigation is to discern the efficacy of incorporating the Problem Based Learning (PBL) model in IPAS lessons on the scholastic accomplishments of students in class V SD 5 Jurang. Employing a qualitative methodology, this study draws its research material from the academic outcomes of students in class V SD 5 Jurang. The participants of this research comprise all students in class V SD 5 Jurang, encompassing a total of 8 students. The data collection techniques employed in this study encompass observation, interviews, documentation, and field notes. The findings of this research evince that the students' academic achievements prior to the implementation of the Problem Based Learning (PBL) model yielded an average pretest score of 50 (moderate), whereas the average posttest score of the class amounted to 71.87 (moderate). Although classified as moderate, the average class score has exhibited a noticeable enhancement. Consequently, it may be discerned that the implementation of the Problem Based Learning (PBL) model in IPAS learning can enhance the academic outcomes of students in class V SD 5 Jurang.